PENGUKUHAN HEGEMONI SOSIO-BUDAYA MELAYU DALAM SRENGENGE - Wahid, Azhar; Ramli, Fathin Noor Ain (JURNAL MELAYU SEDUNIA, 2019)
The concept of Hegemony refers to the total domination of a nation or group, used to study certain political, cultural and ideological forms in society. In today's context, all socio-cultural forms of society experiencing innovation and changes made for the needs of life are constantly changing but maintains its continuity as depicted by Shahnon Ahmad in the Srengenge. The Hegemonic Functionalism approach is used to analyze the textual quality of the Srengenge whereby shows the strengths of socio-cultural hegemony in the Malay community. The findings show that the socio-cultural uniqueness or sustainability of socio-cultural values of the community is dependent on the consistency, continuity and changes made by the community in accordance with the changes in its environment. The narration in the Srengenge is created through the reality recording and imagination, is not something shocking or something that seems as if it is taking a step backward, but the reality demands that the community reinforce a socio-cultural hegemony that embraces all elements of traditional culture and is strengthened by its religious practice. In summary, social norms known as custom become the core of the traditional cultural heritage depicted in the Strengenge can strengthen the socio-cultural hegemony in the daily life of the Malay community traditions.